La toma de decisiones académicas del estudiantado de la Universidad de La Laguna en la elección de los créditos de libre configuración - Mirian Catalina González Afonso; Pedro Ricardo Álvarez Pérez; Dolores Lidia Cabrera Pérez; José Tomás Bethencourt Benítez (Universidad de La Rioja, 2013)
In the university teaching, the academics decision making is a complex process by the great diversity options existent and also by the results that are derived of the achieved choice. In this paper is analized several personal, academic and contextual variables that affect the choice of free shape credit. An exhaustive analysis is carried out with a wide sample of students of the Education Higher Centre at the University of La Laguna to know the criterion that are take into account, the process that is achieved, and the satisfaction degree with the choice. The results are useful to understand how the students to bring face yours academics decision making, and to implement the appropiate guidance that promote good choices.